Perception, Attitude, and Student Awareness in Working on Online Tasks During the Covid-19 Pandemic - Maison Maison; Dwi Agus Kurniawan*; Lika Anggraini (Universitas Syiah Kuala, 2021)
Pandemic Covid-19 requires people to carry out their activities from home, or in other words, online. Likewise, all educational activities are carried out online to avoid and break the pandemic virus's transmission chain. This study examines the effect of students’ perceptions and attitudes on student awareness of doing online assignments due to the spread of the Covid-19 pandemic affecting learning in education. Learning that initially took place traditionally (face to face) shifted to virtual learning (online learning). The research method uses mixed methods with a sequential explanatory design with a total sample of 312 students of physics education at the University of Jambi. The instruments in this study used questionnaires and interviews. The data will be analyzed using SPSS 21. The research results show that students' perceptions, attitudes, and awareness in carrying out their assignments online are in a good category. This fact shows a significant effect of perceptions and attitudes on students' awareness of doing assignments online. It is evidenced by the effect of 70.5% of students 'perceptions and attitudes on students' awareness of doing assignments online. The remaining 29.5% is influenced by other variables not found in this study.